When, where and how should we assess professionalism in undergraduate medical education? Practical tips from an international conference roundtable discussion [version 1; peer review: 1 approved, 2 approved with reservations] - Caitlin Patterson; Scott Oliver; Alexandra Goodwin; Catherine Paton; Kathleen Collins (MedEdPublish)
The assessment of professionalism in healthcare disciplines is a challenging and nuanced topic in medical education. The literature, although continually emerging, remains in its infancy in regards to the role of the assessment of professionalism, appropriate timing for assessment, methods to assess professionalism and the benefits and implications of assessment of professionalism. With emergence of healthcare professionalism in both undergraduate and postgraduate curricula and increasing awareness of professionalism’s pertinent role in developing as a healthcare practitioner, the concept of assessing this topic is being discussed regularly in international fora, but as yet there is no consensus decision in how best to proceed. The authors have over a decade of experience researching, promoting and delivering healthcare professionalism education. They presented a roundtable discussion to an international panel of medical educators at an international conference. The attendees represented multiple healthcare disciplines. Breakout rooms and pre-determined introductory questions were used to explore the international consensus on current thinking about assessment in healthcare professionalism. This paper presents these findings as practical tips for educators who are considering introducing or extending their assessment of undergraduate professionalism, all of which were taken from the main themes of the discussion. The aim of the paper is to support educators to think about their stance on this often divisive issue, consider their approaches and focus future research to clarify the remaining unknowns.